Dispersal, distribution and genetic diversity of Melampyrum subalpinum group - Chlumský, Jan (Jihočeská univerzita, 2016)
This thesis is focused on the dispersal, distribution, and genetic diversity of the taxonomically highly diverse Melampyrum subalpinum group. A complete revision of the localities of M. subalpinum in the Czech Republic and Slovakia is presented. The genetic variation and population structure of the M. subalpinum group across its distribution range is described based on allozymes, nuclear and chloroplast gene sequencing, and genome size. Signs of historical hybridization with M. nemorosum were found in some populations. A comparison of seed dispersal by ants between the co-occurring M. subalpinum and M. pratense and the influence of differences in this process are presented. A new mean of seed dispersal (endozoochory) is introduced for Melampyrum. Myrmecochorous dispersal distances are tested and Holocene migration possibilities are discussed taking into account endozoochory.
Dispersal, distribution and genetic diversity of Melampyrum subalpinum group
Keywords: Orobanchaceae; Melampyrum subalpinum; seed dispersal; endozoochory; myrmecochory; genetic diversity; population genetics; allozymes; genome size; phylogeography; hybridization; cpDNA; nrDNA; Orobanchaceae; Melampyrum subalpinum; seed dispersal; endozoochory; myrmecochory; genetic diversity; population genetics; allozymes; genome size; phylogeography; hybridization; cpDNA; nrDNA